Proteasome inhibitors attenuated cholesterol-induced cardiac hypertrophy in H9c2 cells - Lee, Hyunjung; Park, Jinyoung; Kim, Eunice EunKyeong; Yoo, Young Sook; Song, Eun Joo (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2016)
The Ubiquitin proteasome system (UPS) plays roles in protein degradation, cell cycle control, and growth and inflammatory cell signaling. Dysfunction of UPS in cardiac diseases has been seen in many studies. Cholesterol acts as an inducer of cardiac hypertrophy. In this study, the effect of proteasome inhibitors on the cholesterol-induced hypertrophic growth in H9c2 cells is examined in order to observe whether UPS is involved in cardiac hypertrophy. The treatment of proteasome inhibitors MG132 and Bortezomib markedly reduced cellular surface area and mRNA expression of beta-MHC in cholesterol-induced cardiac hypertrophy. In addition, activated AKT and ERK were significantly attenuated by MG132 and Bortezomib in cholesterol-induced cardiac hypertrophy. We demonstrated that cholesterol-induced cardiac hypertrophy was suppressed by proteasome inhibitors. Thus, regulatory mechanism of cholesterol-induced cardiac hypertrophy by proteasome inhibitors may provide a new therapeutic strategy to prevent the progression of heart failure.